Quality of acute stroke care in Korea (2008–2014): Retrospective analysis of the nationwide and nonselective data for quality of acute stroke care. (December 2019) - Park, Hong-Kyun; Kim, Seong-Eun; Cho, Yong-Jin; Kim, Jun Yup; Oh, Hyunji; Kim, Beom Joon; Kang, Jihoon; Lee, Keon-Joo; Jang, Min Uk; Park, Jong-Moo; Park, Kwang-Yeol; Lee, Kyung Bok; et al.
Background: There is limited information about non-selective and contemporary data on quality of stroke care and its variation among hospitals at a national level. Patients and methods: We analysed data of the patients admitted to 258 acute stroke care hospitals covering the entire country from the Acute Stroke Quality Assessment Program, which was performed by the Health Insurance Review and Assessment Service from 2008 to 2014 in South Korea. The primary outcome measure was defect-free stroke care (all-or-none), based on six get with the guidelines-stroke performance measures (except venous thromboembolism prophylaxis). Results: Among 43, 793 acute stroke patients (mean age, 67 ± 14 years; male, 55%), 31, 915 (72.9%) were hospitalised due to ischaemic stroke. At a patient level, defect-free stroke care steadily increased throughout the study period (2008, 80.2% vs. 2014, 92.1%), but there were large disparities among hospitals (mean = 50.7%, SD = 21.7%). Defect-free stroke care was given more frequently in patients being treated in hospitals with 25 or more stroke cases per month (odds ratio [OR] 2.83; 95% confidence interval [CI] 1.69–4.72), delivery of intravenous thrombolysis one or more times per month (OR 2.37; 95% CI 1.44–3.92), or provision of stroke unit care (OR 1.75; 95% CI 1.22–2.52). Discussion: This study shows that the quality of stroke care in Korea is improving over time and is higher in centres with a larger volume of stroke or intravenous thrombolysis cases and providing stroke unit care but hospital disparities exist. Conclusion: Reducing large differences in defect-free stroke care among acute stroke care hospitals should be continuously pursued.